Authority of Revocation of Mining Business Permits in the Perspective of Administrative Law Towards Good and Environmentally Friendly Mining Governance - Wahyu Nugroho; Liza Marina; Dessy Sunarsi (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The President's authority to revoke thousands of mineral and coal Mining Business Permits (IUPs) is part of the efforts of a Good & Environmentally Friendly Mining Governance system. In the management of natural resources, aspects of environmental sustainability are needed. The research method used is normative juridical, with qualitative data analysis techniques. The results of this study are: first, the mechanism for revocation of IUP through a comprehensive evaluation from planning to post-mining activities, based on administrative, technical, environmental, and financial evaluations. The criteria for IUPs to be revoked are IUPs that do not submit Work Plan and Cost Budget reports, IUPs that are not operating, and IUPs that do not carry out post-mining reclamation obligations, and do not carry out environmental management. Second, the revocation of an IUP has three implications, namely juridical implications, namely policies for regulating and improving the mining governance system. The sociological implications are getting the social carrying capacity of the community and access to natural resource management rights. Finally, the implications of environmental insight, as a global commitment to implementing sustainable development principles, are integrated into the mining business activity licensing system.